Redundant Roles of SMAD2 and SMAD3 in Ovarian Granulosa Cells In Vivo - Li, Qinglei (American Society for Microbiology (ASM), 2008)
Transforming growth factor β (TGF-β) superfamily members are critical in maintaining cell growth and differentiation in the ovary. Although signaling of activins, TGF-βs, growth differentiation factor 9, and nodal converge preferentially to SMAD2 and SMAD3, the in vivo functions and redundancy of these SMADs in the ovary and female reproduction remain largely unidentified. To circumvent the deleterious phenotypic aspects of ubiquitous deletion of Smad2 and Smad3, a conditional knockout strategy was formulated to selectively inactivate Smad2, Smad3, or both Smad2 and Smad3 in ovarian granulosa cells. While granulosa cell ablation of individual Smad2 or Smad3 caused insignificant changes in female fertility, deletion of both Smad2 and Smad3 led to dramatically reduced female fertility and fecundity. These defects were associated with the disruption of multiple ovarian processes, including follicular development, ovulation, and cumulus cell expansion. Furthermore, the impaired expansion of cumulus cells may be partially associated with altered cumulus expansion-related transcripts that are regulated by SMAD2/3 signaling. Our results indicate that SMAD2 and SMAD3 function redundantly in vivo to maintain normal female fertility and further support the involvement of an intraovarian SMAD2/3 pathway in mediating oocyte-produced signals essential for coordinating key events of the ovulatory process.